O ensino de desenho. Saberes e práticas das professoras de artes: um olhar... muitas possibilidades... - França, Léa Carneiro de Zumpano (2006)
The current study, of qualitative approach, investigates the knowledge of four art teachers belonged to the municipal network of teaching with the purpose of comprehending the theoretical bases and the built experiences in drawing teaching, intending to answer the following questions: What drawing conceptions support their actions in the classroom? How, when and with what objective the drawing is proposed to the students of the firsts grades of Elementary School of the municipal network of teaching in Uberlândia? Based in the works of Derdyk (1989), Frange (1995), Morais (1995), Buosso (1990), Artigas (1999), Motta (1967) and Amílcar de Castro (1999), the aim of this study approaches the drawing as knowledge, language, expression, communication, register, representation, project, invention and designation. Our study uses as theoretical reference Tardif (2002), Zabala (1998), C. Gauthier (1998), B. Charlot (2000), Freire (2004) and Hernández (2005), in the perspective that significant practices are built in everyday constructions of teacher s doing. We assume that the drawing teaching in the art classes, given by teachers graduated in Arts Education who are compromised with their continuous formation by participating in group of studying and/or researching, as well as experience in teaching, can become more significant for the student in consequence of its constitution and specificity of this content. From the reports of the collaborators, this study searches to analyze and discuss the data about the conceptions which permeate the educative work with drawing, its teaching and what methodology paths subsidize these actions. The answers presented by the teachers reveal that they comprehend the drawing in several conceptions, suchlike project, register, representation, language, expression, and stages of creative process. Besides, the answers have showed diversity of pedagogic tracks, such as teach by thematic propositions, discuss stereotypic, proposes drawing tracks by the graphic or figurative references and the elements of visual language, and also the use of alternative materials. The results of this research indicate as significant and important are the doing and saying built by the teachers, for, furthermore delineating their conceptions about the drawing teaching, and they become the start point to promote dialogue between the educational proposals and the educative practices in the Art teaching, as well as to incentive their continuous formation, the way of being a teacher, of teaching and learning how to draw.